2021
DOI: 10.1016/j.scitotenv.2020.141816
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight ultraviolet radiation dose is negatively correlated with the percent positive of SARS-CoV-2 and four other common human coronaviruses in the U.S.

Abstract: Human coronaviruses are RNA viruses that are sensitive to ultraviolet (UV) radiation. Sunlight contains UVA (320–400 nm), UVB (260–320 nm) and UVC (200–260 nm) action spectra. UVC can inactivate coronaviruses, including severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). The incidence and mortality of coronavirus disease 2019 (COVID-19) are considered to be correlated with vitamin D levels. Vitamin D synthesis in human skin is closely related to exposure to UVB radiation. Therefore, the incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
2
42
0
1
Order By: Relevance
“…Accordingly, it was found that the ultraviolet radiation caused a decrease in COVID-19 reported cases in São Paulo, Brazil. Among different wavelengths of ultraviolet light, the 200–260 nm range is able to damage pathogens RNA or DNA ( Tang et al, 2020 ). Another study indicates 90% the SARS-CoV-2 load can be inactivated after being exposed to the midday summer sunlight for 34 min ( Sagripanti and Lytle, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it was found that the ultraviolet radiation caused a decrease in COVID-19 reported cases in São Paulo, Brazil. Among different wavelengths of ultraviolet light, the 200–260 nm range is able to damage pathogens RNA or DNA ( Tang et al, 2020 ). Another study indicates 90% the SARS-CoV-2 load can be inactivated after being exposed to the midday summer sunlight for 34 min ( Sagripanti and Lytle, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Significant associations between higher UV Index and lower COVID-19 prevalence were observed in Japanese prefectures ( 39 ), and 33 cities in the USA ( 40 ). Some negative associations were also reported for reduced infection rates and increased ambient UV levels measured in 5 Brazilian cities (March–July 2020) ( 41 ) and selected counties of north-east and central-mid-west (census regions 1 and 2) of the USA (April–July 2020) ( 42 ).…”
Section: Uv Light Sun Exposure and Covid-19mentioning
confidence: 90%
“…For example in temperate regions during the summer months, populations spend more time outdoors, as well as ventilating buildings to a greater extent ( RAMP Task 7 Members, 2020 ), both factors that tend to inhibit COVID-19. Likewise, viral degradation due to UV-B radiation in sunlight is greatly increased during the summer months ( Ratnesar-Shumate et al, 2020 ; Schuit et al, 2020 ; Tang et al, 2020 ), as are vitamin D levels due to exposure to sunlight ( Tang et al, 2020 ; Whittemore, 2020 ). Furthermore, the effect of low air temperatures and VP levels during winter on the respiratory tract should not be ignored.…”
Section: Discussionmentioning
confidence: 99%